2023
DOI: 10.1186/s12885-022-10458-x
|View full text |Cite
|
Sign up to set email alerts
|

Patient perspectives on considerations, tradeoffs, and experiences with multiple myeloma treatment selection: a qualitative descriptive study

Abstract: Background Advances in multiple myeloma treatment and a proliferation of treatment options have resulted in improved survival rates and periods of symptom-free remission for many multiple myeloma patients. As a result, health-related quality of life (HRQoL) concerns related to myeloma treatments have become increasingly salient for this patient population and represent an important consideration guiding patients’ treatment choices. To gain an understanding of patients’ experiences with choosing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
2
3
1
Order By: Relevance
“…Many patients reported that they would consider changing current treatment for a new therapy if the new therapy has a potential to double the remission time, is fully covered by their insurance, or markedly reduce SE burden, indicating patients' desire to improve quality of life and reduce cost and disease burden while living longer. This finding is consistent with other studies on patient perspectives conducted in the US ( 19 ) and other countries ( 4 , 20 22 ). While efficacy has been consistently identified as the most important factor when choosing MM treatment options, a variety of other factors influence patients' decision-making, including quality of life and tolerability of SEs ( 19 , 21 23 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Many patients reported that they would consider changing current treatment for a new therapy if the new therapy has a potential to double the remission time, is fully covered by their insurance, or markedly reduce SE burden, indicating patients' desire to improve quality of life and reduce cost and disease burden while living longer. This finding is consistent with other studies on patient perspectives conducted in the US ( 19 ) and other countries ( 4 , 20 22 ). While efficacy has been consistently identified as the most important factor when choosing MM treatment options, a variety of other factors influence patients' decision-making, including quality of life and tolerability of SEs ( 19 , 21 23 ).…”
Section: Discussionsupporting
confidence: 93%
“…This finding is consistent with other studies on patient perspectives conducted in the US ( 19 ) and other countries ( 4 , 20 22 ). While efficacy has been consistently identified as the most important factor when choosing MM treatment options, a variety of other factors influence patients' decision-making, including quality of life and tolerability of SEs ( 19 , 21 23 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Qualitative studies in chronic haematological malignancies such as MM and MDS have examined treatment decision‐making, 7,8 prognosis, 9 and distress 10 . Qualitative studies in MM spanned a range of areas including younger patients, longer‐term survivors, and cognitive impairment 11 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, the immune checkpoint inhibitor therapy patients interviewed by Cappelli et al 32 expressed fear and uncertainty about the treatment and the impact of side effects on their quality of life. Dombeck et al 33 found that, when making treatment decisions, patients with multiple myeloma tried to balance treatment efficacy with quality of life. Ihrig et al 34 pointed out that German patients’ expectations of immunotherapy may sometimes be unrealistic.…”
Section: Introductionmentioning
confidence: 99%